أستنباط طريقة جديدة لحل كيناميتيكية مجاميع التروس المعقدة التركيب - فاهم فخري الحمداني; سعد نجيب شهاب; مهند نزار مصطفى (Journal of Engineering and Sustainable Development, 2011)
This work contains a general study about all epicyclic gear trains .This was accomplished by:-1.Developing simplified equations for the kinematic analysis of all epicyclic gear trains .This will be used for future steady state and dynamic analysis .2.Utilizing the developed equations as a model for solving the kinematics of all epicyclic gear trains .This can be applied in all complex gear trains by developing a new approach which is regarded as an equivalent system using an imaginary method . 3.Using the new equivalent method to understand the kinematics of all complex gear trains which are difficult to analyse . This is achieved by simplifying all complex gear trains into simple epicyclic gear trains by re-drawing the new equivalent system . The basic aim of this paper is to develop a new and simple learning technique in understanding and solving the kinematics of any complex gear mechanism . In addition , this approach might be useful in future design of complex gear mechanism .